2017
DOI: 10.1128/jvi.02421-16
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence-Independent, Unstructured Internal Ribosome Entry Site Is Responsible for Internal Expression of the Coat Protein of Turnip Crinkle Virus

Abstract: To maximize the coding potential of viral genomes, internal ribosome entry sites (IRES) can be used to bypass the traditional requirement of a 5= cap and some/all of the associated translation initiation factors. Although viral IRES typically contain higher-order RNA structure, an unstructured sequence of about 84 nucleotides (nt) immediately upstream of the Turnip crinkle virus (TCV) coat protein (CP) open reading frame (ORF) has been found to promote internal expression of the CP from the genomic RNA (gRNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 62 publications
(81 reference statements)
0
28
0
Order By: Relevance
“…Thus, an unstructured element embedded in an RNA structure may actually be the driving force of a structured motif. In the case of IRESs, this notion could provide an explanation for the discovery of short linear poly(U) motifs that harbour IRES activity 144 , for the finding that the ITAF PTB recognizes and binds to a polypyrimidine-rich motif, (CCU) n , in structured cellular IRESs 114 , or for the detection of an unstructured region that is important for the activity of the turnip crinkle virus IRES 190 , despite the fact that viral IRESs are thought to largely be structured. Thus, local mRNA structures as well as unstructured motifs therein can regulate translation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an unstructured element embedded in an RNA structure may actually be the driving force of a structured motif. In the case of IRESs, this notion could provide an explanation for the discovery of short linear poly(U) motifs that harbour IRES activity 144 , for the finding that the ITAF PTB recognizes and binds to a polypyrimidine-rich motif, (CCU) n , in structured cellular IRESs 114 , or for the detection of an unstructured region that is important for the activity of the turnip crinkle virus IRES 190 , despite the fact that viral IRESs are thought to largely be structured. Thus, local mRNA structures as well as unstructured motifs therein can regulate translation.…”
Section: Discussionmentioning
confidence: 99%
“…However, apparently this observation has not been repeated in other labs (e.g., Fan et al, 2012). A low level of CP translation from genomic RNA of carmoviruses Hibiscus chlorotic ringspot virus (HCRSV) (Koh et al, 2003;Fernández-Miragall and Hernández, 2011), Pelargonium flower break virus (PFBV) (Fernández-Miragall and , and Turnip crinkle virus (TCV) (May et al, 2017) has also been reported to be IRESmediated. Like the crTMV IRES, the TCV IRES seems to require only to be A-rich and lack of structure and its activity is inversely correlated with the size of the RNA.…”
Section: Intergenic Region Enhancersmentioning
confidence: 96%
“…Furthermore, enhancement of IRES function in the presence of 3′-poly(A) and the absence of 5′-cap suggest a crosstalk between PABP, the CrTMV IRES and the 3′-poly(A) tail ( Marom et al, 2009 ). Similarly, an unstructured sequence of about 84 nt has been reported to control low levels of translation of the genomic RNA of turnip crinkle virus (TCV) coat protein ( May et al, 2017 ). Surprisingly, in marked contrast to most IRES elements, this A-rich sequence promotes translation irrespectively of the orientation in eIF4G-dependent but in a 4E-independent manner.…”
Section: Internal Initiation Mechanisms: Rna Structural Motifs Involvmentioning
confidence: 99%